Monitoring Vigilance during Single and Serial Visual Evoked Potentials - Pottinger, R. (Methods of Information in Medicine, 1994)
Full- and half-field visual evoked potentials (VEPs) are used to evaluate functional effects of optic chiasm compression by pituitary tumours. Reduction in VEP amplitude, typically from the temporal fields of vision, can occur even without demonstrable clinical deficit. An inherent problem of prolonged or serial testing is that changing levels of vigilance may affect the VEP. Gradual decrease in vigilance during a test sequence or with serial testing may cause a reduction in amplitude of the response mimicking the abnormality sought. This has serious implications when monitoring the effect of medical treatment since it may give a false impression of tumour growth requiring urgent surgery to prevent blindness. This report illustrates the nature of the problem and describes techniques using electroencephalograms (EEG), which have been used in an attempt to monitor vigilance. The ultimate aim is to produce a system to automate such monitoring during VEP recording.
Keywords: EEG; Evoked Potentials; Vigilance; Monitoring